Lipidomic and metabolomic characterization of a genetically modified mouse model of the early stages of human type 1 diabetes pathogenesis - Overgaard, Anne Julie (Metabolomics, 2015)
The early mechanisms regulating progression towards beta cell failure in type 1 diabetes (T1D) are poorly understood, but it is generally acknowledged that genetic and environmental components are involved. The metabolomic phenotype is sensitive to minor variations in both, and accordingly reflects changes that may lead to the development of T1D. We used two different extraction methods in combination with both liquid- and gas chromatographic techniques coupled to mass spectrometry to profile the metabolites in a transgenic non-diabetes prone C57BL/6 mouse expressing CD154 under the control of the rat insulin promoter (RIP) crossed into the immuno-deficient recombination-activating gene (RAG) knockout (−/−) C57BL/6 mouse, resembling the early stages of human T1D. We hypothesized that alterations in the metabolomic phenotype would characterize the early pathogenesis of T1D, thus metabolomic profiling could provide new insight to the development of T1D. Comparison of the metabolome of the RIP CD154 × RAG(−/−) mice to RAG(−/−) mice and C57BL/6 mice revealed alterations of >100 different lipids and metabolites in serum. Low lysophosphatidylcholine levels, accumulation of ceramides as well as methionine deficits were detected in the pre-type 1 diabetic mice. Additionally higher lysophosphatidylinositol levels and low phosphatidylglycerol levels where novel findings in the pre-type 1 diabetic mice. These observations suggest that metabolomic disturbances precede the onset of T1D. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s11306-015-0889-1) contains supplementary material, which is available to authorized users.